Improvement of Negative Electrodes for Iron-Air Batteries: Comparison of Different Iron Compounds as Active Materials. Issue 2 (10th January 2019) - Rodríguez, H. A. Figueredo; McKerracher, R. D.; de Leόn, C. Ponce; Walsh, F. C.
Abstract : For iron-air batteries, it has yet to be established which iron-containing material is the best candidate for producing iron electrodes. Galvanostatic charge-discharge cycling up to a potential of −0.55 V vs. Hg/HgO was carried out for at least 20 cycles on steel mesh-coated hot pressed iron electrodes. Five different iron active materials were tested: carbonyl iron, Fe3 O4 (magnetite), Fe2 O3 (hematite), FeOOH (goethite) and iron sulfide, resulting in five hot pressed electrodes. In addition, five hot pressed electrodes were prepared using the same iron active materials but with further processing by ball milling. The specific capacity and voltage of the electrodes is compared, where possible, with similar iron electrodes reported in the literature. This paper reports the maximum, mean value and standard deviation of the specific discharge capacity for each electrode; the highest mean discharge capacity was achieved with the ball milled Fe3 O4 electrode with a value of 610 mA h g −1 Fe . The shortest formation period was observed for the goethite iron electrode, which achieved a maximum discharge capacity after just 3 cycles with a standard deviation of only 9 mA h g −1 Fe over 21 cycles.